Inadequate protein and milk consumption related to stunting in children aged 24–59 months in Tanjung Priok, Jakarta - Sheila Octavia; Sandra Fikawati; Aurelia Yoshadara (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Evidence on the combined association of nutrient intake and specific protein-source foods with stunting in densely populated Indonesian urban communities is limited, hindering the implementation of locally targeted nutritional interventions. This study aimed to examine the association between nutrient intake and protein-source food consumption and stunting among children aged 24–59 months in Tanjung Priok, North Jakarta. Methods: This cross-sectional study included 184 children selected by cluster random sampling from three subdistricts between January and July 2023. Stunting was defined as a height-for-age below −2 standard deviations of the World Health Organization growth standard. Dietary intake was assessed using a 24-hour recall and protein-source food frequency questionnaire. Chi-square tests and logistic regression were used to analyzed. Of the 184 children, 43 (23.4%) were stunted. Rare milk and dairy consumption (<4 times/week) was associated with higher odds of stunting (adjusted odds ratio [aOR], 2.911; 95% confidence interval [CI], 1.260–6.723; p=0.012). Inadequate protein intake was also associated with higher odds (aOR, 2.268; 95% CI, 1.024–5.023; p=0.044). Other adjusted dietary associations were not found to be statistically significant. In conclusion, rare milk and dairy consumption and inadequate protein intake were associated with stunted growth. Improving access to affordable and diverse protein-rich foods, including appropriate dairy products, may support child nutrition in similar urban communities.